Inconsistent time preferences and on-the-job search - when it pays to be naive - Matthias Fahn; Regina Seibel (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study optimal employment contracts for present-biased employees who can conduct on-the-job search. Presuming that firms cannot offer long-term contracts, we find that individuals who are naive about their present bias will actually be better off than sophisticated or time-consistent individuals. Moreover, they search more, which partially counteracts the inefficiencies caused by their present bias.
Keywords: D21; D83; D90; J31; J32; 330; present bias; on-the-job search